The Research of Welding Residual Stress Based Finite Element Method - Qinghua Bai (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Welding residual stress was caused by local heating during the welding process, tensile residual stress reduce fatigue strength and corrosion resistance, Compressive residual stress decreases stability limit. So it will produce brittle fracture, reduce working life and strength of workpiece; Based on the simulation of welding process with finite element method, calculate the welding temperature field and residual stress, and then measure residual stress in experiments, So as to get the best welding technology and welding parameters, to reduce welding residual stress effective, it has very important significance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2661